The Effectiveness of Group Counseling with Reframing Technique to Promote Psychological Well-Being of - Huda, Nurul; Eddy Wibowo, Mungin; Murtadho, Ali (Universitas Negeri Semarang, 2022)
Psychological well-being affects one’s feeling and behavior. Thus, this study attempted to examine the effectiveness of group counseling with reframing technique to improve the psychological well-being of the grade eight students of SMP Almunawir Batang. It used reframing intervention for six sessions and a pretest-posttest design which was analyzed using Wilcoxon test. Of initially 135 students, eight containing four male students and four female students were chosen to be the subjects of this study. Findings showed that the group counseling with reframing technique is effective to promote psychological well-being. Consequently, reframing technique can be said effective to improve this variable, and counselors are suggested to apply this treatment to improve students’ psychological well-being.